The celebrity endorsement industry: adapting to Web 2.0 and beyond - Raphael, Jackie (Curtin University, 2013)
The Hollywood entertainment industry and celebrity status has had a global impact on advertising and consumption since its emergence in the early 20th century. However, the advent of the Internet and social media has transformed popular culture. With YouTube having exceeded two billion views a day in May 2010 (Timeline 2010), more than one billion people active on Facebook since October 2012 (Newsroom: Timeline 2012), and social network advertising revenues estimated to reach $10 billion globally by 2013 (Social Network Ad Revenues to Reach $10 Billion Worldwide in 2013 2011), it is clear that there has been a paradigm shift in the way people communicate and how they are entertained. These changes are having huge effects on the advertising industry and celebrity industry.Case studies of Hollywood identities Pamela Anderson, Leonardo DiCaprio and Ashton Kutcher illustrate the changes that have occurred to how a celebrity brand can be initiated and maintained. The complex interaction of celebrity identity, choice of endorsement and control of access to the means of publication are also examined. Social media statistics, semiotic analysis of online branding, the application of Grant McCracken’s meaning transfer theory to endorsements and interviews with industry professionals are used to investigate this relationship, revealing themes of convergence, adaptation, authenticity, credibility, iconic status and branding. It is concluded that Web 2.0 has transformed the nature of celebrity-fan interaction and consumer-advertiser communication, and is significantly shifting media control and censorship away from businesses and government, towards celebrities and their audiences.